Schumpeter Finanzberatung GmbH : evaluating investment risk - Petersen, Mitchell A. ([London] : SAGE, 2016)
It is April 2014, and the small investment management firm Elke Schumpeter founded twelve years earlier in Frankfurt, Germany, is performing well. The fund, Schumpeter Finanzberatung GmbH (SF), has pursued a low-cost market timing (tactical asset allocation) strategy that targets a mix of 60% in the equity market index and 40% in German treasury bills (T-bills) but that also strategically changes the mix in an attempt to beat the passive benchmark. This case explains how the fund has outperformed the passive benchmark by 98 basis points.
Originally Published in: Petersen, M. A. (2015). Schumpeter Finanzberatung GmbH: Evaluating Investment Risk. 5-314-503. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Risk management -- Case studies; Investment analysis -- Case studies; Asset-backed financing -- Case studies